Spray-synthesized organic composite/hydroxyapatite coating on magnesium alloys with enhanced corrosion resistance - Wang, Guoqiang; Wei, Yi; Hong, Jinquan; Lv, Jiangquan (Frontiers in Chemistry, 2025)
The development and production of anti-corrosive coatings are critical for medical implants, particularly those that utilize composite coatings made from both flexible organic materials and rigid inorganic materials, which exhibit advantageous mechanical properties and resistance to corrosion. In this work, an organic composite/hydroxyapatite (HA) coating on magnesium alloys is fabricated through a two-step process, which involves the application of a spray technique for the organic silica composite [polyethyleneimine (PEI)/silica sol (Si)], followed by a hydrothermal treatment to deposit hydroxyapatite. The dense and tight layer-by-layer assembly of the PEI/Si/HA coating on the Mg substrate exhibited a corrosion current density of 10−5.6 A/cm2, significantly lower than that of HA and the Mg substrate. After immersion for 13 days, the PEI/Si/HA coatings demonstrated a minimal amount of H2 generation and negligible fluctuations in pH within the solution. Meanwhile, the hydrothermal PEI/Si/HA coatings exhibited significantly weaker corrosion resistance than the PEI/Si/HA coatings synthesized using the spray method. Both electrochemical dynamic data and structural characteristics demonstrate the enhanced corrosion resistance of organic composite/hydroxyapatite coatings, in which polymer chains provided more volume as a buffer for H2 molecules. This organic composite/hydroxyapatite coating on magnesium alloys exhibited huge potential applications in orthopedics.